Prognostic implication of transforming growth factor alpha in adenocarcinoma of the lung--an immunohistochemical study. - Tateishi, M. (1991)
We examined for transforming growth factor alpha (TGF alpha) in adenocarcinomatous lesions of the lung tissues excised from 138 patients, with use of the avidin-biotin-peroxidase complex (ABC) method. TGF alpha was present in the cytoplasm of the adenocarcinoma. Our objective was to determine if TGF alpha could serve as a prognostic parameter. We divided 138 patients into two groups according to the concentration of TGF alpha. Ninety-two patients had a high concentration of TGF alpha, in over 75% of the tumour cells, while 46 had a low concentration, that is in less than 75% of the cells. The 5-year survival rates of patients with high TGF alpha and low TGF alpha were 39% and 64%, respectively (P less than 0.05). Our data suggest that evidence of a high immunoreactivity of TGF alpha can serve as a prognostic parameter in adenocarcinoma of the lung.